Non-conventional Yeast Species for Lowering Ethanol Content of Wines - Ciani, Maurizio; Morales, Pilar; Comitini, Francesca; Tronchoni, Jordi; Canonico, Laura; Curiel, José A.; Oro, Lucia; Rodrigues, Alda J.; Gonzalez, Ramon (Frontiers in Microbiology, 2016)
Rising sugar content in grape must, and the concomitant increase in alcohol levels in wine, are some of the main challenges affecting the winemaking industry nowadays. Among the several alternative solutions currently under study, the use of non-conventional yeasts during fermentation holds good promise for contributing to relieve this problem. Non-Saccharomyces wine yeast species comprise a high number or species, so encompassing a wider physiological diversity than Saccharomyces cerevisiae. Indeed, the current oenological interest of these microorganisms was initially triggered by their potential positive contribution to the sensorial complexity of quality wines, through the production of aroma and other sensory-active compounds. This diversity also involves ethanol yield on sugar, one of the most invariant metabolic traits of S. cerevisiae. This review gathers recent research on non-Saccharomyces yeasts, aiming to produce wines with lower alcohol content than those from pure Saccharomyces starters. Critical aspects discussed include the selection of suitable yeast strains (considering there is a noticeable intra-species diversity for ethanol yield, as shown for other fermentation traits), identification of key environmental parameters influencing ethanol yields (including the use of controlled oxygenation conditions), and managing mixed fermentations, by either the sequential or simultaneous inoculation of S. cerevisiae and non-Saccharomyces starter cultures. The feasibility, at the industrial level, of using non-Saccharomyces yeasts for reducing alcohol levels in wine will require an improved understanding of the metabolism of these alternative yeast species, as well as of the interactions between different yeast starters during the fermentation of grape must.